2020
DOI: 10.1590/0004-282x20190152
|View full text |Cite
|
Sign up to set email alerts
|

Free carnitine and branched chain amino acids are not good biomarkers in Huntington’s disease

Abstract: Background: Huntington’s disease (HD), caused by an expanded CAG repeat at HTT, has no treatment, and biomarkers are needed for future clinical trials. Objective: The objective of this study was to verify if free carnitine and branched chain amino acids levels behave as potential biomarkers in HD. Methods: Symptomatic and asymptomatic HD carriers and controls were recruited. Age, sex, body mass index (BMI), age of onset, disease duration, UHDRS scores, and expanded CAG tract were obtained; valine, leucine, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Genetically it is associated with the expansion of cytosine adenine guanine trinucleotide repeats in the Huntingtin gene [ 41 , 42 ]. There is no treatment available for the management of HD, although in pre-clinical studies several flavonoids have shown promising protective effects against HD, e.g., hesperidin and naringin in a rat model of HD [ 43 ]. Other studies conducted on quercetin, rutin, and myricetin have also reduced the symptoms of HD in animal models of the disease [ 44 , 45 ].…”
Section: Flavonoids and Neuroprotectionmentioning
confidence: 99%
“…Genetically it is associated with the expansion of cytosine adenine guanine trinucleotide repeats in the Huntingtin gene [ 41 , 42 ]. There is no treatment available for the management of HD, although in pre-clinical studies several flavonoids have shown promising protective effects against HD, e.g., hesperidin and naringin in a rat model of HD [ 43 ]. Other studies conducted on quercetin, rutin, and myricetin have also reduced the symptoms of HD in animal models of the disease [ 44 , 45 ].…”
Section: Flavonoids and Neuroprotectionmentioning
confidence: 99%